Cognitive Reserve in Model Systems for Mechanistic Discovery: The Importance of Longitudinal Studies - McQuail, Joseph A.; Dunn, Amy R.; Stern, Yaakov; Barnes, Carol A.; Kempermann, Gerd; Rapp, Peter R.; Kaczorowski, Catherine C.; Foster, Thomas C. (Frontiers in Aging Neuroscience, 2021)
The goal of this review is to provide a resource for longitudinal studies, using animal models, directed at understanding and modifying the relationship between cognition and brain structure and function over the course of life. We propose that forthcoming longitudinal studies will build upon a wealth of knowledge gleaned from prior cross-sectional designs in order to identify early predictors of variability in cognitive function during aging, and characterize fundamental neurobiological mechanisms that underlie the vulnerability to, and the trajectory of, cognitive decline. Finally, we present examples of biological measures that may differentiate mechanisms of cognitive reserve at the molecular, cellular, and network level.